Differential impact of independent and interdependent views of the self on the use of consensus and heterogeneity information: the case of validity of groups’ decisions - Lopes, D. (2017)
In this article, we analyse the moderating effect of the activation of independent and interdependent views of the self on the use of heterogeneity and consensus information in the attribution of validity to group decisions. In two experimental studies, we present evidence showing that the participants, when primed with an interdependent view of the self, make no distinction between homogeneous or heterogeneous information regarding group composition while attributing validity to group decisions. Indeed, they base their validity attribution mainly on consensus information. In contrast, when primed with an independent view of the self, they make use of variability information as they attribute a greater validity to a more heterogeneous and consensual group and a lower validity to a group depicted as homogeneous and consensual. Results are discussed in light of the differential utility of consensus and heterogeneity information, as well as participants’ self-knowledge within the processes of validation of group decisions.